2008
DOI: 10.1159/000142133
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Perception of Information and Experiences of Nuchal Translucency Screening in Greece

Abstract: Objective: First trimester ultrasound (US) screening has become part of antenatal care. The aim of this study was to explore pregnant women’s perceptions of the information given and experiences of first trimester nuchal translucency (NT) screening and to identify the background factors in a woman’s biography that influence her information needs and experiences of NT screening. Methods: This study was a descriptive, prospective survey which involved collecting information from the participants by using a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…A study in Athens similarly showed that most women did not have much knowledge, specifically about the purposes and the diagnostic limitations of NT screening (Gourounti et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A study in Athens similarly showed that most women did not have much knowledge, specifically about the purposes and the diagnostic limitations of NT screening (Gourounti et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…PST include first‐trimester screening [nuchal translucency (NT) ultrasound with or without testing of the mothers’ blood] and second‐trimester screening (triple test) (Gourounti et al . , Sahin & Gungor , Pieters et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…the possibility of something going wrong with the baby), possibility of miscarriage, the issue of birth and financial issues were the major worries for Greek pregnant women. The prevailing worry about the baby's health may be attributed to prenatal screening (Gourounti et al, 2008;Petersen et al, 2009). This finding was in agreement with the findings of previous studies (Statham et al, 1997;Georgsson Ö hman et al, 2003;Petersen et al, 2009;Carmona Monge et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, scre- ening tests with reliable results should be performed at an early stage in pregnancy. We aimed to identify an anomalous baby at an early stage with the help of the combined screening tests (weeks [11][12][13][14], the triple screening tests (weeks [15][16][17][18][19][20], noninvasive advanced ultrasonographic examination and invasive tests such as chorionic villus sampling (CVS) or amniocentesis. The advancements in biochemical markers and imaging technologies have enabled us to detect fetal chromosomal abnormalities in the early weeks of pregnancy [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…The choice of test depends on the obstetric assessment protocols of the region or country, and on the demographical and sociocultural features of the women 12,13 . This study was planned to evaluate the pregnant women's knowledge, thoughts and attitudes about noninvasive tests used for the detection of fetal chromosomal abnormality risk in the first and second trimesters of pregnancy.…”
Section: Introductionmentioning
confidence: 99%